SIMBOLISME WARNA DAN MOTIF DALAM SARUNG ADAT TENUN SUKU KUI KECAMATAN ALOR BARAT DAYA KABUPATEN ALOR - Maria Delia B. Tukan; Matheos E. Maure, Marni S. Laure, Mehelina R. Lebo, Mariam Atamai, Marsalina Malaikari, Salmon Wenig (JOURNAL OF COMMUNITY DEDICATION, 2025)
This study aims to examine the Symbolism of Colours and Motifs in the Traditional Weaving Sarong of the Kui Tribe, Southwest Alor District, Alor Regency which is a cultural heritage that has historical, social and economic values. The research technique used in this research is qualitative description, interviews with community stores Oma Siti Hasan and Oma Maimuna Bukelo. The results of this study indicate that the Kui Tribe community of Southwest Alor District still has a culture that is still maintained until now, this is marked by the existence of woven sarong as one of the traditional objects that is very important and must be used in every procession or adatiah ritual such as engagement, customary fines, to death. Woven sarongs have names, motifs, colours and meanings. The woven sarong of the Kui Tribe is a woven fabric that is unique and has its own cultural value for the local community. Each motif has a deep meaning.